Comparative Evaluation of Rumen Responses, Blood and Serum Indices in Murrah Buffaloes, Vrindavani and Tharparkar Cattle on a Similar Diet - Narayana Rathode; A. K. Verma; Anju Kala; Payal Agarwal; H. Rahman; Chaudhary, L. C. (Indian Journal of Animal Nutrition, 2023)
Rumen microbial ecosystem is a complex, highly diversified microenvironment comprised of bacteria, protozoa, archaea, fungi and phages which enables ruminants to utilize poor quality fibrous feed. Comparison between cattle and buffalo for the rumen metabolism is challenging and interesting to understand.With this background information, the present study has been carried out by conducting a feeding trial of 120 days to compare rumen fermentation, microbial profile and blood indices in Murrah buffalo (n=6), Vrindavani (n=6) and Tharparkar (n=6) cattle on a similar diet. The daily dry matter intake (kg/d) was higher (P